E-Service Quality, E-Trust and E-WOM in increasing E-Customer Loyalty Lazada - Umdatul Umah; Alshaf Pebrianggara; Muhammad Yani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
The rapid growth of the online marketplace has created competition between marketplaces in Indonesia. The emergence of various new marketplaces that are growing now allows consumers to move from one platform to another. This challenge must be faced by marketplaces in maintaining consumer loyalty. The purpose of this study was to determine the effect of e-service quality, e-trust and e-WOM on Lazada e-customer loyalty. This research is a descriptive research using quantitative methods. The population of this study is users of the Lazada marketplace in Sidoarjo. Sampling using non-probability sampling techniques with purposive sampling techniques with a total sample of 96 people. Data analysis technique using Partial Least Square using Smart-PLS 3.0 program. The results of this study indicate that e-service quality, e-trust and e-wom partially affect e- loyalty.